How can the sustainable goal of cultivated land use in the Qinghai-Tibet Plateau be realized?—based on a research framework of cultivated land use patterns - Wang, Ximeng; Zhou, Dingyang; Jiang, Guanghui; Peng, Chen (Frontiers in Environmental Science, 2023)
The study of cultivated land use models is an important means to improve the benefit of cultivated land use and promote the sustainable use of cultivated land. The rational optimization of regional cultivated land use models based on the consideration of regional background conditions and development goals can provide a scientific basis for ensuring the sustainable use of cultivated land. The three-dimensional research framework of "natural quality - utilization intensity - spatial layout" of cultivated land use patterns was constructed. Taking the county as a unit, the natural quality, spatial distribution and utilization intensity of cultivated land in the Qinghai Tibet Plateau were evaluated, and the types of cultivated land utilization models were determined. Based on the ecological protection and the regulation and control of agriculture and animal husbandry in the Qinghai Tibet Plateau, the optimization direction of cultivated land use patterns was discussed. The results show that the cultivated land use pattern divided by the "NUS" three-dimensional model can accurately reflect the characteristics of cultivated land use in the Qinghai Tibet Plateau. The existing cultivated land use pattern in the Qinghai Tibet Plateau is basically consistent with its ecological protection and development direction zoning, but the problems of unreasonable expansion and excessive use intensity of cultivated land exist in the ecotone between some development areas and restricted areas. The research suggests that the utilization and optimization of cultivated land in the Qinghai Tibet Plateau should be based on the premise of protecting ecological security and striving to solve the contradiction between agricultural development and ecological protection to realize the sustainable utilization of cultivated land.